EndoBind detects endogenous protein-protein interactions in real time - Anke Bill (Nature Portfolio, 2021)
Bill et al describe two high-throughput methods to detect protein-protein interactions in cells in real-time using the split-NanoLuciferase-complementation system. They demonstrate the methods can detect exogenously (RT-bind) or endogenously (EndoBind) expressed proteins, respectively.